KEPUASAN KERJA PENDIDIK PROFESIONAL DALAM PERSPEKTIF PSIKOLOGI - Budi Setia Baskara; Iis Farida Zein; Dian Anggraeni; Asep Ikhwan Awaluddin; Teddy Suryana (Fakultas Agama Islam Universitas Wiralodra, 2022)
JOB SATISFACTION OF PROFESSIONAL EDUCATORS IN PSYCHOLOGICAL PERSPECTIVE This study aims to determine the concepts, indicators, supporting factors, and efforts to achieve job satisfaction of professional educators from a psychological perspective. This research uses a qualitative approach, library research methods and daily experiences, and content analysis. This study found that from a psychological perspective; (1) the conception of professional educator job satisfaction, both cognitive and affective satisfaction, is the perception and feeling of pleasure experienced by expert educators for their work in educating; (2) the indicators of satisfaction are feeling the fulfillment of expectations, feeling fair treatment, being satisfiers, not dissatisfiers; (3) the supporting factors are internal factors (support in overcoming stress and workload, age, gender) and external factors (support for the suitability of the type of work, work environment and motivation/suggestion, organizational culture, subjective well-being, and transformational leadership style ); and (4) efforts to achieve it are rights and obligations balancing, factor conditioning, trust building, communication sustainability, and togetherness building.